Integrasi Madzhab Humanistik dengan Nilai-Nilai Islam dalam Pembentukan Kepribadian guru - Siti A’yunuttazkiyah; Elsy Yulia Rahmani; A’lal Aqil; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2026)
This article discusses the integration between the humanistic school in educational psychology and Islamic values in shaping the teacher’s personality. The humanistic approach emphasizes self-actualization, learning freedom, and appreciation of human potential, while Islamic values highlight the purification of the soul (tazkiyatun nafs), moral development, and exemplary character. This study employs a qualitative descriptive literature review method to examine the relevance of both approaches. The findings indicate that integrating the humanistic perspective with Islamic values can produce holistic teachers—intellectually intelligent, emotionally mature, morally upright, and spiritually aware. This integration broadens the function of education from merely transferring knowledge to a comprehensive process of personality formation and spiritual development for educators..